Reflect Method Action to develop capacities in business and tax management - Collantes Palomino, Hugo Yvan (2016)
The present research has as general objective to determine to what extent the application of the Reflect Action Method achieves the development of capacities in business and tributary management of the farmers of Monsefú, Reque and Eten; And as specific objectives: perform the validity and reliability test of the data collection instruments, apply the pretest and post test to evaluate the capacities in Business and tax management, apply the Reflect action. This research is important because the literacy method and its approach, influences the significant learning of business and tax management among illiterate people. In this perspective, a pre - research was developed, the data collection was carried out by applying a pre - test and a post to the sample, the research development was approached from an educational perspective, observing the current situation of the peasants, with Regarding the development of capacities of the business and tax management.